SINTAKTIK STILISTIK VOSITALARNING IJTIMOIY TARMOQ PLATFORMALARDA QOʻLLANIShI (Facebook va Instagram misolida) - Qobilova, M.Sh. (SCIENCE and SOCIETY, 2025)
This article analyzes the use of syntactic stylistic devices in social media texts and their rhetorical impact. The research is primarily based on the Facebook and Instagram platforms. The study focuses on various artistic expression tools – particularly rhetorical questions, parallelism, ellipsis, inversion, and several other devices – and discusses their role in enhancing the expressiveness of speech, engaging readers, and effectively conveying messages.
Keywords: syntactic stylistic devices; Facebook platform; rhetorical questions; parallelism; ellipsis; inversion; user-generated content